On the determination of defect dipoles from atomistic simulations using periodic boundary conditions - Pasianot, Roberto Cesar (2016)
By solving the problem of a periodic distribution of point defects in general anisotropic media, we give an alternative, more direct proof, of the relatively recent procedure that extracts dipole tensors from the stress acting on the cell of atomistic simulations performed under periodic boundary conditions. Moreover, we show that naive superposition of individual defect fields is not a solution of the problem, though correction terms can be identified; as a byproduct, analysis of the latter allows us to reveal a spurious contribution to the elastic interaction energy as calculated in current literature procedures, that therefore must be subtracted in order to obtain correct results.